Cartilage Thickening in Early Radiographic Human Knee Osteoarthritis –Within-Person, Between-Knee Comparison - Cotofana, Sebastian (2012)
OBJECTIVE: To determine whether the presence of definite osteophytes (in absence of joint space narrowing [JSN]) by radiograph is associated with (subregional) increases in cartilage thickness, in a within-person, between-knee cross-sectional comparison of participants in the Osteoarthritis Initiative (OAI). Based on previous results, external medial (ecMF) and external lateral weight-bearing femoral (ecLF) subregions were selected as primary endpoints. METHODS: Both knees of 61 (of 4798) OAI participants displayed definite tibial or femoral marginal osteophytes and no JSN in one knee, and no signs of radiographic OA in the contra-lateral knee; this being confirmed by an expert central reader. In these participants, cartilage thickness was measured in 16 femorotibial subregions of each knee, based on sagittal DESSwe magnetic resonance images. Location-specific joint space width from fixed flexion radiographs was determined using dedicated software. Location-specific associations of osteophytes with cartilage thickness were evaluated using paired t-tests and mixed effect models. RESULTS: Of the 61 participants, 48% had only medial, 36% only lateral, and 16% bi-compartmental osteophytes. Osteophyte knees had significantly thicker cartilage than contra-lateral non-osteophyte knees in the ecMF (+71±223μm, equivalent to +5.5%, p=0.015) and ecLF (+64±195μm, +4.1%, p=0.013). No significant differences between knees were noted in other subregions, nor in joint space width. Cartilage thickness in ecMF and ecLF was significantly associated with tibial osteophytes in the same (medial or lateral) compartment (p=0.003). CONCLUSION: Knees with early radiographic OA display thicker cartilage than (contra-lateral) knees without radiographic findings of OA, specifically in the external femoral subregions of compartments with marginal osteophytes.